Recording the dynamic polarisation gratings in pure nematic liquid crystal - Slussarenko, Sergei S.; Melnikova, Elena A.; Tolstik, Alexei L. (Journal of the Belarusian State University. Physics, 2022)
We report on experimental realisation of polarisation dynamic gratings recording in pure nematic liquid crystal. This work is devoted to the experimental implementation of writing polarisation dynamic gratings in a pure nematic liquid crystal. The registration mechanism is based on the photorefractive effect in a cell filled with a pure nematic crystal under the action of an applied constant electric field. This phenomenon does not require the presence of photoexcited charge carriers in the liquid crystal and is explained by the extremely high anisotropy of the liquid crystal. The article provides an elementary theoretical model of this process. The dependences of the grating writing process on the spatial frequency of the interference field and the intensity of the recording beams are investigated. It was found that the spatial grating does not coincide with the interference field – the response of the medium is non-local. However, we do not associate this property with that in photorefractive crystals. In our case, a mechanism of purely geometric mismatch is more likely due to the peculiarity of the recording mechanism. One of the fundamental properties of the described processes is their independence from the wavelength of the recording radiation, which confirms the model of the recording mechanism we have chosen.
Keywords: liquid crystals; photorefractivety; holography